Transforming treatments for schizophrenia: Virtual reality, brain stimulation and social cognition. (June 2020) - Gainsford, Kirsten; Fitzgibbon, Bernadette; Fitzgerald, Paul B; Hoy, Kate E
Highlights: Poor social cognition in schizophrenia significantly impacts daily functioning Current social cognitive therapies are intensive with modest functional outcomes Virtual reality allows treatment in controlled, life-like, therapeutic environments Brain stimulation can enhance neuroplasticity and directly affect pathophysiology Combined virtual reality and brain stimulation may enhance social cognitive therapy Abstract: Schizophrenia is characterised by delusions, hallucinations, anhedonia and apathy; while impairments in social cognition are often less recognised. Poor social cognition can lead to difficulties in obtaining and maintaining employment, academic progression, interpersonal relationships, and community functioning. Current interventions are highly intensive, require significant resources and have only modest effects on functional outcomes. Virtual reality (VR) and non-invasive brain stimulation (NIBS) may have a role in addressing these limitations. VR allows treatments that are potentially more accessible, less delivery intensive, and have higher ecological validity. While NIBS is able to directly modulate activity in social brain areas in order to promote neuroplasticity, strengthen neural connections and enhance brain function related to social cognitive behaviours. Therefore, the combination of VR and NIBS may allow for more efficient and transferrable interventions than those currently available. This review will explore the potential role of these technologies in the treatment of social cognitive impairment.